Enhanced electromagnetic wave absorption performance of SiCN(Fe) fibers by in-situ generated Fe3Si and CNTs. Issue 14 (15th July 2021) - Feng, Yurun; Guo, Xue; Lu, Junbin; Liu, Jie; Wang, Guantong; Gong, Hongyu
Abstract: The SiCN(Fe) fibers with excellent one-dimensional microstructure and electromagnetic wave (EMW) absorption performance were synthesized by combining polymer-derived ceramics (PDCs) method and electrospinning. The in-situ generation of Fe3 Si and CNTs by adding ferric acetylacetonate (FA) into the raw materials effectively improved the dielectric properties, magnetic properties and the impedance matching performance of the SiCN(Fe) fibers. The EMW absorption performance of SiCN(Fe) fibers were mainly based on dipole polarization loss, interface polarization loss and eddy current loss. The RLmin value of SiCN(Fe) fibers reached −47.64 dB at 1.38 mm and the effective absorption band (EAB, RL ≤ −10 dB) reached 4.28 GHz (13.72–18 GHz, 1.35 mm).